On classification of degenerate singular points of Ricci flows - Аbiev, N.А. (Karaganda State University Publ., 2015)
We consider the normalized Ricci flow on generalized Wallach spaces that could be reduced to a system of nonlinear ODEs. As a main result we get the classification of degenerate singular points of the system under consideration in the important partial case a . In general the problem can also be considered as two-parametric bifurcations of solutions of abstract dynamical systems. Thus the problem un-der investigation is interesting not only in geometrical sense, but concerns the theory of planar dynamical sys-tems.
Риччи ағымдарының өзгешеленген ерекше нүктелерін классификациялау туралы
О классификации вырожденных особых точек потоков Риччи
Keywords: Riemannian invariant metric; Einstein metric; generalized Wallach space; Ricci flow; dynamical system; system of nonlinear ordinary differential equations; singular point; degenerate singular point; para-metric bifurcations